(untitled) (Physical Education, Health and Social Sciences, 2025)
This research primarily focuses on ageing, disintegrated function, and age-related diseases such as T2D. Telomere shortening, mitochondrial dysfunction, and oxidative stress drive ageing, resulting in cellular and metabolic decay. Researchers have identified the downregulation of the MIPEP gene as a factor involved in these processes, which is relevant to mitochondrial health and cellular metabolism. The research unveils the modulation of MIPEP using the computational CRISPR-Cas9 technique as a preclinical solution for ageing-related impairments. Upregulation of MIPEP improves mitochondrial quality, decreases oxidative stress, and preserves pancreatic β-cells important for insulin synthesis and glucose control. Exercising the mitochondria may thereby slow the shortening of telomeres, another ageing biomarker associated with cellular senescence and metabolic dysfunction due to MIPEP activation. Furthermore, the role of MIPEP activation for important signalling pathways like Insulin Signaling, arginine metabolism, AMPK and Akt signalling pathways involved in energy regulation and β-cell survival is presented in the research. This research may present a unique approach to addressing T2D and other geriatric diseases given that they focus on the primary processes of ageing: mitochondrial malfunctioning and telomere shortening. The results highlighted the importance of mitochondrial quality of life in ageing and offered a platform for developing targeted medicine for ageing and ageing diseases.